Interlinguistic Intertwining in Songs: Dāstān in the Repertoire of the Bards of Iranian Khorasan - Youssefzadeh, Ameneh (Traditiones, 2023)
Centuries of intense cultural exchange between speakers of Turkic and Iranian languages have made northern Khorasan, a region in north-eastern Iran, a significant field for the study of interlinguistic intertwinings in songs. In this article, I examine multilingualism in an important performance genre called dāstān or hekāyat (“story” or “tale”) which plays a central role in the repertoire of Khorasan bards known as bakhshi. These performers are trilingual and sing in Persian, Khorasani Turkish, and Kurmanji Kurdish, the languages of the various ethnic groups living in the area for centuries. In performing a dāstān, the bakhshis alternate sections of spoken prose (in Persian, Khorasani-Turkish, or Kurmanji Kurdish, depending on the audience) with verses (usually in Khorasani-Turkish) sung to their accompaniment on the dotār (a long-necked lute with two strings). I will observe several performances of the dāstān “Shāh Esmā’il and Golzār Khānum”.